Kepemimpinan K.H. Abdul Aziz dalam Meningkatkan Kualitas Hafalan Al-Qur’an Santri di Pondok Pesantren Misbahunnur Kota Cimahi - Hidayat, Mochamad Nur (Tadbir: Jurnal Manajemen Dakwah, 2025)
This study aims to determine the interpersonal role, informational role, decision making of K.H. Abdul Aziz's in improving students' Qur’anic memorization quality using descriptive qualitative methods through participatory observation, interviews, and documentation. The research aims to identify interpersonal rol as a leader, he serves as an exemplar by providing direct motivation, and effective communication with various stakeholders. In his informational role, he filters and delivers beneficial information while developing innovative learning strategies. As a decision-maker, he applies democratic principles and consultation, ensuring all initiatives support the pesantren's primary objective of improving students' Qur'anic memorization quality.